Peran OKKPD Provinsi Sumatera Utara Dalam Penanganan Isu Hoaks Beras Plastik Terhadap Keamanan dan Kepercayaan Konsumen - Suraya, Rani; Syahla, Aufaa; Rangkuty , Meisa Putri; Hasibuan , Ade Degisqi Maharani; Nurfadhilah, Apnisa; Nasution , Muhammad Shofwan Rusdy (Yayasan Jompa Research and Development, 2025)
The hoax issue regarding plastic rice circulating in the community has caused unrest and reduced consumer confidence in food safety, especially rice. This study aims to analyze the role of the Regional Food Safety Competent Authority (OKKPD) in addressing the plastic rice hoax issue and its impact on food safety and consumer confidence. The research method used a qualitative descriptive design through observation, interviews, and documentation during an internship at the UPTD for Food Crop and Horticulture Protection and Quality Control of North Sumatra Province. Data were analyzed descriptively with an emphasis on the OKKPD's work mechanisms in the pre-market and post-market stages. The results show that OKKPD plays an active role through field rice sampling, laboratory testing, pre-market audits, and public clarification. The laboratory test results confirmed the absence of plastic content in the tested rice, thus proving the issue false. Although the monitoring mechanism is functioning well, low public information literacy allows hoaxes to spread easily and influence public perception. In conclusion, the OKKPD's role is very important in maintaining food safety and restoring consumer confidence, but public education efforts and socialization of the use of the SIPSAT application are needed.